Characterization of maternal health in Santa Maria, RS. 2005-2009 - Juliana Falcão Padilha; Lourdes Boufleur Farinha; Karen Mello de Mattos; Andriele Gasparetto (Universidade Federal de Santa Maria, 2012)
Objectives: relate the maternal variables coming from the Information System of Live Births (SINASC) from Santa Maria-RS, linked in the live births's health, as: maternal age, among another. Method: this study was developed with a quantitative descriptive approach, using secondary data obtained in the basis of DATASUS. The data were collected from March to May of 2011. Results: in the period between 2005 and 2009 were registered 16504 live births in Santa Maria, being 62,37% of cesarian and 37,63% vaginal; 49,23% of the live births were from women between 20-30 years; 65,36% of the women had seven or more prenatal visits; and the higher education level, the higher the rate of cesarean. Conclusions: there was a significant increase in cesarean section among young postpartum women. It is necessary more studies to be outlined the profile of this population group and generate effective locoregionais strategies